Non Genetic Factors Affecting Pre-Weaning Weight and Growth Rate of Ettawah Grade Goats - A Sodiq (Media Peternakan, 2012)
The present study was carried out to evaluate the effect of various non-genetic factors on live weights at different ages (at birth, 30, 60, 90, and 120 d of age), and on average daily gains (from birth to 30, 60, 90, and 120 d) of Ettawah Grade kids. Data from 314 records kids at the national village breeding centre of Kaligesing Purworejo Central Java province were analyzed. Results showed that average live weights at birth (BW= 3.44 kg), 30 d of age (W30= 7.19 kg), 60 d of age (W60= 11.05 kg), 90 d of age (W90= 14.75 kg), 120 d of age (W120= 18.86 kg), and average daily gain from birth until 30 d of age (ADG30= 125.6 g), 60 d of age (ADG60= 126.97 g), 90 d of age (ADG90= 125.87 g), 120 d of age (ADG120= 128.78 g) were influenced by sex, litter size, and age of dams. Means of BW, W30, W60, W90, W120, ADG30, ADG60, ADG90, and ADG120 of males were higher than females. Multiple (twin and triplets) born kids were lighter than single. Mean of body weight and average daily gain increased with the dam's age. The implication of these findings should be accounted in genetic evaluations and also should consider maternal ability for the improvement of Ettawah Grade.